Effectiveness and Safety of Infliximab in Two Cases of Severe Chondrocalcinosis: Nine Years of Follow-Up - Jácome Bruges-Armas; Bruno F. Bettencourt; Ana R. Couto; Manuela Lima; Ana M. Rodrigues; Nathan Vastesaeger; Matthew A. Brown (Case Reports in Rheumatology)
Objectives. To investigate the efficacy of infliximab in the treatment of severe calcium pyrophosphate deposition diseases (CPPD). Methods. Two patients with severe CPPD and diffuse idiopathic skeletal hyperostosis- (DISH-) like phenotype are described. Both patients were resistant to therapy with nonsteroidal anti-inflammatory drugs (NSAIDs). Both patients were treated with infliximab, a TNF-α receptor antagonist, for nine years. Results. Treatment with infliximab resulted in major clinical and laboratory improvements without relevant side effects. Conclusions. These results suggest that infliximab may be an effective treatment of severe CPDD.